Evolution of Escherichia coli to Macrophage Cell Line - Miskinyte, Migla (2014)
The genomes of species of Escherichia coli (E. coli) show an extraordinary amount of diversity, which include commensal strains and strains belonging to different pathovars. Many strains of E. coli, which can cause mild or severe pathologies in humans, have a commensal ancestor. Understanding the evolutionary changes that can lead to a transition from commensal to pathogen is an important task, which requires integration of different methodologies. One method is experimental evolution of bacteria, in controlled environments, that mimic some of the selective pressures, likely to be important during the transition to pathogenesis. The success of such a transition will depend, at least partially, on ability of E. coli to adapt to the presence of cells of the immune system. Here, we describe a protocol for performing experimental evolution of a commensal strain of E. coli, a derivative of the well studied K12, under the constant selective pressure imposed by cells of the innate immune system, specifically RAW 264.7 murine macrophage cell line.